Texture Profile Analysis (TPA) of the jelly dessert prepared from Halal gelatin extracted using High Pressure Processing (HPP) - Yusof, Nurlina; Jaswir, Irwandi; Jamal, Parveen; Jami, Mohammed Saedi (International Institute for Halal research and Training (INHART), IIUM, 2018)
Texture Profile Analysis (TPA) is an instrumental analysis on the textural behaviour of food products. It has been used widely in the food industry and provides an indication of panellist sensory evaluation. In this study, the performance of the gelatin extracted from red tilapia fish skin treated with High Pressure Processing (HPP) has been evaluated using TPA method in comparison with the commercial red tilapia fish gelatin. The jelly dessert was made using lychee juice and the sensory texture such as hardness, crispness, adhesiveness, fracturability and chewiness were described based on the force-time plot obtained from TPA test. The results have shown that the hardness, adhesiveness, gumminess and chewiness of the jelly prepared using HPP-treated gelatin are higher compared to commercial gelatin. This is because the gelatin extracted using HPP has higher gel strength. In contrast, the cohesiveness and the springiness are similar for both jellies. In conclusion, jelly prepared using gelatin treated with HPP is preferable compared to commercial gelatin because the gummy is being more rigid, firm and adhesive.